Application of Artificial Intelligence Technology in the Agricultural Field - Wang, Yue (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the rapid development of artificial intelligence (AI) technology, its application in agriculture is continuously expanding, bringing new intelligent and precise solutions to agricultural production. The continuous development of artificial intelligence technology has brought great changes and opportunities to the agricultural field.This paper discusses the current status of artificial intelligence technology in agriculture and its significant implications for sustainable agricultural development. It reviews the applications of artificial intelligence technology in agriculture, including pest and disease prediction, soil and crop monitoring, agricultural robots, and decision support systems. It also analyzes the technical challenges faced (such as data processing capability, algorithm accuracy, data security, and privacy protection) and social and ethical challenges (such as changes in the role of farmers, fairness in data usage). Solutions to these challenges are proposed, emphasizing the crucial role of policymakers. Overall, the application of artificial intelligence technology in agriculture holds enormous potential to promote agricultural modernization and sustainable development.